Building on a Solid Foundation: Conceptual Mapping Informs Schemas for Relating to God - Lucas A. Keefer; Adam K. Fetterman (Religions, 2022)
How do individuals manage to maintain strong emotional and personal relationships with God, despite the physical (and metaphysical) challenges posed by that task? Past studies show that individuals relate to God in characteristic ways based in part on their God concepts, the ways they internally represent the nature of God. The current manuscript summarizes research suggesting that these concepts arise in part through mapping processes involving metaphor and analogy. This review suggests these cognitive processes influence the content of God concepts that ultimately determine how individuals relate to God. Future research would benefit from considering the important role that basic cognitive mapping plays in far-reaching emotional and behavioral outcomes.